Corporate Governance Disclosure Practices: Evidence from Indonesian Islamic Banks - Hendri Setyawan; Devi Permatasari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The purpose of this study is to investigate corporate governance disclosure practices of Islamic banking in Indonesia. We content analyse the annual reports of Islamic banks in Indonesia in 2010 to 2013. This study used a disclosure index developed by Darmadi (2011) to calculate the extent of corporate governance disclosure. The composite index construction uses 7 dimension of corporate governance mechanism including shariah governance namely shariah supervisory board, board of commissionair, board director, board committee, internal control and external audit, risk management, corporate governance implementaion reporting. The results conclude that the 11islamic banks in 3 years adhere to 71% of attributes of the corporate governance disclosure index. Keywords: corporate governance disclosure, Islamic banking